FOLLICULITIS DECALVANS: A CASE REPORT - Arbeláez-Eslait, Sergio A.; Esmeral-Atehortúa, Koretta; Peluffo-Vergara, Sebastián (Revista de la Asociación Colombiana de Dermatología y Cirugía Dermatológica, 2020)
Introduction: Folliculitis decalvans is a rare variant of neutrophilic cicatricial alopecia that consist of areas of central scarring alopecia and tuft follicles surrounded by recurrent follicular pustules; they mainly affect the vertex and the temporo-parietal junction of the scalp. The case of a 20-year-old patient is discussed, with a history of multiple pustules with subsequent evolution to alopecic plaques of variable size and shape, with a generalized location throughout the entire scalp.